Recovery of surface state bands after desorption of Te capping layer on (Bi1−xSbx)2Te3 ternary topological insulators. (19th September 2019) - Kremer, Geoffroy; Zhu, Kejing; Pierron, Thomas; Fournee, Vincent; Ledieu, Julian; Andrieu, Stéphane; Kierren, Bertrand; Moreau, Luc; Malterre, Daniel; He, Ke; Xue, Qi-Kun; Fagot-Revurat, Yannick; et al.
Abstract: Te capping layer on topological insulator (TI) surface provides an efficient way for the protection of surface from oxidation. However, when using Te to protect the surface of (Bi1− x Sb x )2 Te3 ternary topological insulators, it is still unclear for the influence of Te on the surface chemical composition and the surface state bands after the procedure of capping and desorption of Te. Here, we have performed a systematic study of the surface morphology, crystallinity, chemical composition as well as the band structure of (Bi1− x Sb x )2 Te3 after the desorption of the Te capping layer. Our results confirm a good recovery of the surface state bands of the (Bi1− x Sb x )2 Te3 ternary topological insulators with different Bi and Sb compositions. The chemical composition of (Bi1− x Sb x )2 Te3 remains almost unchanged after the desorption of Te. This study proves that the Te capping layer works as a suitable protection for ternary (Bi1− x Sb x )2 Te3 TI layers, allowing for ex situ transfer of TI samples in air. This opens the way for the development of metal/TI hybrid structures for advanced spintronic applications.